DESIGN OF PHYSICAL MODEL TEST OF NATURAL COASTAL PROTECTION SYSTEM: A CASE STUDY OF EFFECT OF SLOPE GRADIENT OF THE GEOBAG STRUCTURE ON WAVE TRANSMISSION IN NATURAL COASTAL PROTECTION SYSTEM - Wono Saputra, Novianto
Erosion is one of the serious problems that occur in coastal areas and it can cause the coastal damage. There are many of methods that can be used to control the erosion, one of them is natural protection system. One of natural protection system that can be used in coastal protection are mangroves. Mangroves are considered quite effective, efficient, and environmetally friendly in preventing erosion in coastal are areas. But in the proccess of planting and growing of mangroves seedlings, which need to be considered is environmental condition for mangroves to grow well. Therefore, it is neccessary to protect the seeds of mangrove that is being grown. One of the most effective, easy-to-make, and modelable physical, is the geobag structure. In this final project, physical model test of natural coastal protection system consisting of a permanent coastal protection is mangrove and temporary coastal protection is a geobag structure. The modelling scenario is done by changing the slope/gradient of geobag structure and the variation of wave parameters that generated by wavemaker. The scale used in this project is 1 : 10. There are 9 kinds of waves are generated by wavemaker that use to test the coastal protection system. The result of physical test is wave height and wave period from visual observation and wave recorder result. The wave recorder data is validated with visual observation data to obtain the height and wave period for further analysis. From the height and the period that have been validated, will be obtained value of transmission coefficient (Kt) in each scenario. The lowest of Kt values are the Kt values of scenario with slope/gradient of structure is 1:1.5. This Final Project si also looking for the relation between transmission coefficient with dimensionless variables that generated by Phi Buckingham method. The higher the slope/gradient of geobag structure, the value of transmission coefficient is higher, so that the structure is more uneffective.